2010
DOI: 10.1038/eye.2010.52
|View full text |Cite
|
Sign up to set email alerts
|

Subjective evaluation of intraoperative performance of DisCoVisc in complex ocular environments

Abstract: Purpose To subjectively evaluate the intraoperative characteristics of DisCoVisc during phacoemulsification in complex ocular environments. Patients and methods In this prospective observational study, two experienced surgeons (ARV and CZ) performed phacoemulsification on 100 consecutive patients with cataract associated with complex ocular environments. Inclusion criteria were eyes with shallow anterior chambers (anterior chamber depth (ACD) of o2.1 mm), inadequate pupillary dilation (3 mm), dense cataract, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…One previous study (24) evaluating DisCoVisc in complex ocular environments showed that this OVD facilitated good intraoperative performance in complex cases and was effective in simple cataract surgeries; however, this study was observational and non-comparative.…”
Section: Discussionmentioning
confidence: 88%
“…One previous study (24) evaluating DisCoVisc in complex ocular environments showed that this OVD facilitated good intraoperative performance in complex cases and was effective in simple cataract surgeries; however, this study was observational and non-comparative.…”
Section: Discussionmentioning
confidence: 88%